Conceptualising relevant social context indicators for people receiving home care: A multi‐method approach in Flanders, Belgium. (6th August 2021) - Van Doren, Shauni; Hermans, Kirsten; Declercq, Anja
Abstract: Despite an increasing awareness of the impact of the social context of a person on personalised care planning, there is currently no generally accepted classification of social context. As a result, home care professionals have a partial understanding of what social context is and how it affects and can even benefit their work. In this study, we define the main themes and concepts of the social context in the home care setting. The goal in this study is twofold. Initially, we want to offer a multidimensional and practical model of social context, founded on the perspectives of care users and professional caregivers in home care. This model of social context, in turn, will be the foundation for the development of a Social Supplement for the interRAI assessment instruments. We conducted nine focus groups in Flanders between September and November 2017. Fifty‐four people participated. The focus groups followed a semi‐structured format based on themes identified from the literature and three in‐depth interviews with experts. Questions focused on defining the main themes of 'social context' and their subcategories. At the end of each discussion, participants were asked to consider which concept could be suitable and essential for a Social Supplement to the current interRAI instruments. Focus groups were recorded, transcribed and analysed using NVivo. We used investigator and theoretical triangulation to ensure the quality of our analysis, and identified five overarching themes of social context; (a) care and support, (b) physical environment, (c) life and care goals, (d) psychosocial well‐being and (e) civic engagement. These main themes were mentioned throughout the nine focus group discussions, even though a diverse group of stakeholders participated. This model provides the basis for the development of a Social Supplement for the interRAI assessment instruments in Flanders, Belgium.